PENGARUH KEPATUHAN TERHADAP SOP KEUANGAN DAN PENGAWASAN AUDITOR INTERNAL TERHADAP EFEKTIVITAS PENGGUNAAN DANA PADA KB NU MAYANGAN - Nur Lailatul Azhima; Aulia Fachreza Ulfa; Gunawan Aji (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of compliance with financial Standard Operating Procedures (SOPs) and internal auditor supervision on the effectiveness of fund utilization at KB NU Mayangan. This research uses a qualitative descriptive approach to obtain in-depth understanding of how procedures and internal supervision operate within financial management practices. Data were collected through in-depth interviews, observation of financial administration activities, and documentation related to institutional financial records. The results show that consistent implementation of financial SOPs and optimal internal auditor supervision play an essential role in improving transparency, accountability, and effectiveness of fund utilization. The study also found that strong internal control mechanisms can minimize errors and potential misuse of funds, thus supporting the improvement of the quality of educational services at KB NU Mayangan.